2023
DOI: 10.1029/2022jd037949
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of Isolated Deep Convection Initiation and Its Relation to Topography in the North China Area

Guilin Lu,
Yangze Ren,
Shizuo Fu
et al.

Abstract: This study investigates the statistical characteristics of isolated deep convection initiation (DCI) and its relation to topography in the North China area during the summer season of 2017–2019. A total of 2,534 isolated DCI events are identified using the infrared brightness temperature data from Himawari‐8 satellite with a resolution of 0.05° × 0.05°. The spatial distribution of DCI shows clustering over mountains and hills, indicating that the local topography may be critical for DCI. Topography is describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
(170 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have shown that larger SCCs are more likely to develop into deep convective clouds [9], and Figure 8 suggests that deep convective clouds tend to form near the top of the mountains. This is consistent with the results of previous studies [29,43].…”
Section: The Variation Of Cloud Numbers and Sizes With The Elevationsupporting
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown that larger SCCs are more likely to develop into deep convective clouds [9], and Figure 8 suggests that deep convective clouds tend to form near the top of the mountains. This is consistent with the results of previous studies [29,43].…”
Section: The Variation Of Cloud Numbers and Sizes With The Elevationsupporting
confidence: 94%
“…If the air is sufficiently humid, clouds are produced when the upslope winds meet near the tops of the mountains. Both observational studies [27][28][29] and modelling studies [30,31] confirm that clouds prefer to develop near mountain tops. Note that these studies are mostly concerned with deep convective clouds instead of SCCs.…”
Section: Introductionmentioning
confidence: 88%